Forging strategic alliances: the agency of human–algorithmic curation under conditions of Platform Capitalism - Gaia Tedone (Journal of Science and Technology of the Arts, 2019)
Under conditions of so-called “Platform Capitalism”, software and algorithms undertake the important task of designing the interaction amongst online users and establishing criteria of relevance for content. As such, they operate as curatorial agents of platforms’ content, establishing what is there to see, know and consume. This state of affairs calls for a revision of the traditional role of the (human) curator who is confronted with an online environment characterised by the unprecedented collision of commercial, aesthetic, cultural and political interests. The question of what kind of relationship the curator shall create with the algorithm then becomes crucial: is this a relationship of antagonism, resistance or alliance? How do these two curatorial agents influence each other? In this article, I analyse a cluster of hybrid artistic and curatorial experiments (including my own curatorial work) that foregrounds online platforms as discrete modes of socio-technical assemblages that curate particular forms of connectivity amongst networks of users, data layers and technical infrastructures. By doing so, I argue for the forging of strategic alliances between human and machinic curators as a strategy to channel new forms of creativity and cooperation under conditions of “Platform Capitalism” and to operationalise human-algorithmic curation as a political and aesthetic practice within the networked culture.